Analisis Peran Grup “Info Cegatan Jogja” dalam Upaya Penyelesaian Permasalahan Tarif Parkir “Nuthuk” di DIY - Miftahul Ahsan, Muhammad; Permatasari, Ane (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
Info Cegatan Jogja (ICJ) group or community has an important role in the lives of the people of Yogyakarta as a place to discuss, interact, and convey aspirations through social media posts. Of the various types of posts in ICJ, one of the posts that is still often found is posts related to the issue of "Nuthuk" parking rates in DIY. The frequent occurrence of this problem is one of the interesting things to be researched and studied. Therefore, this research aims to analyze the role of the ICJ group itself in efforts to solve the "Nuthuk" parking tariff problem. In conducting the research, a descriptive qualitative method and case study approach were used. The results of this study found the fact that the "Info Cegatan Jogja" group has not had an effective role in efforts to resolve the problem of "Nuthuk" parking rates in DIY. Based on the results of interviews with ICJ managers, ICJ once had a strong role in influencing policy before the Covid-19 pandemic. After the pandemic, the function of ICJ itself began to shift only as a forum for exchanging ideas and interacting, not to produce a policy input or policy brief. This has an impact on the role of ICJ which currently tends to focus on community information centers only.